ETIOPATHOGENIC CHARACTERISTICS OF THE INTRAVENTRICULAR HEMORRHAGES IN THE STRUCTURE OF PERINATAL BRAIN INJURIES: A LITERATURE REVIEW AND THE RESULTS OF OWN RESEARCH - B. M. Glukhov; Sh. A. Bulekbaeva; A. K. Baidarbekova (Русский журнал детской неврологии, 2017)
Background. The term «intraventricular hemorrhage of the newborn» was first introduced in the Soviet Union in 1970s. In the first soviet guidelines on pediatric neurology, the intraventricular hemorrhage (IVH) was considered as a complication after birth injury induced by a mechanical trauma to the fetal head due to the choroidal vascular plexus. The first large-scale studies devoted to IVH in children were conducted in the USA in the 1970s after the introduction of ultrasound examination of brain, which is the main instrumental method for IVH diagnostics. In 1978, the specialists manage to explore the germinal matrix of the brain in the fetus and newborn, which is believed to be the main source of IVH in premature newborns. This structure was shown to give rise to brain neuroblasts and glia: this is a capillary-rich area that consists of poorly differentiated randomly arranged cells, and has a soft connective-tissue carcass that can cause IVH in this area in newborns. According to a currently accepted approach, risk factors for IVH are divided into 3 pathogenetic groups: antenatal, intranatal and postnatal. Among the antenatal risk factors, the main role belongs to the prenatal infection, especially viral infection. Besides, mother comorbidities (first of all cardiovascular and endocrine diseases) and pathological pregnancy (threatened abortion, severe gestosis and placental insufficiency) are also considered as important predictors of IVH. The internatal risk factors include placental detachment, precipitate labor, disseminated intravascular coagulation syndrome in mother etc. In this article the authors present a detailed review of currently available data as well as the results of own studies.Objective: to provide an overview of the stages of the IVH investigation, to identify the main features of the IVH etiopathogenesis comparing to other perinatal disorders of the central nervous system, and to assess the consequences of IVH.Materials and methods. The study was based on the results of clinical and pathogenetic investigations of 182 children who underwent rehabilitation in the specialized center for children with nervous system disorders (Astana, Republic of Kazakhstan).Results. In contrast to non-IVH perinatal disorders, the IVH is mostly observed in the premature newborns (63.1 % of cases) with less than 34 weeks of gestational age (22.3 % of cases). The IVH may lead to serious consequences including decreased rehabilitation potential in terms of both anatomical abnormalities and cognitive and speech disorders.Conclusion. We have identified the main features of IVH etiopathogenesis in children, compared them with the features of other perinatal disorders, and evaluated their consequences.